Can We Restart the Recovery All Over Again? - Taylor, John B. (American Economic Review, 2016)
Many have argued that a deviation from good economic policy has been a cause of the poor U.S. economic performance of the past decade and that policy reforms are needed to restore strong growth. Yet others argue that the recent stagnation is secular or that the possibility of a rapid recovery is long gone without more fiscal stimulus. Here I show that unusual economic conditions leave plenty of room for a reform-induced rebound. Taking demographics and the growth of capital services into account, labor force participation and productivity growth are unusually low. Hence, policy reforms could generate a post-recession-like acceleration as well as sustained growth and stability.